Mesilla/Conejos-Médanos Basin: U.S.-Mexico Transboundary Water Resources - Robertson, Andrew J.; Granados-Olivas, Alfredo; Robertson, Andrew J.; Matherne, Anne-Marie; Pepin, Jeff D.; Ritchie, Andre B.; Sweetkind, Donald S.; Teeple, Andrew P.; García-Vásquez, Ana Cristina; Carroll, Kenneth C.; Fuchs, Erek H.; Galanter, Amy E. (2022)
Synthesizing binational data to characterize shared water resources is critical to informing binational management. This work uses binational hydrogeology and water resource data in the Mesilla/Conejos-Médanos Basin (Basin) to describe the hydrologic conceptual model and identify potential research that could help inform sustainable management. The Basin aquifer is primarily composed of continuous basin-fill Santa Fe Group sediments, allowing for transboundary through flow. Groundwater flow, however, may be partially or fully restricted by intrabasin uplifts and limited recharge